Adult weight gain and risk of prostate cancer: A dose–response meta‐analysis of observational studies. Issue 4 (1st October 2015) - Chen, Qi; Chen, Tao; Shi, Wentao; Zhang, Tianyi; Zhang, Wei; Jin, Zhichao; Wei, Xin; Liu, Yuzhou; He, Jia
Abstract : The association between adult weight gain and risk of prostate cancer has not been widely studied and the findings are inconsistent. Therefore, our study aimed to investigate the association between adult weight gain and risk of prostate cancer. PubMed, Embase and Web of Science databases were searched for relevant studies published before September 2014 using terms related to weight gain and prostate cancer. Summary estimates were obtained using the random‐effects model. Dose–response meta‐analysis, sensitivity analysis and publication bias tests were performed. Nine studies involving 497, 634 participants and 22, 338 cancer cases were included. For total prostate cancer, a positive relationship with adult weight gain was observed until weight gain increased to >30 kg. For low‐intermediate‐risk prostate cancer, a positive relationship with adult weight gain was observed until weight gain increased to >15 kg. For high‐risk prostate cancer, we observed a positive linear relationship with adult weight gain with a relative risk (RR) of 1.02 [95% confidence interval (CI) 1.00–1.04] for every 5‐kg increase. For fatal prostate cancer, we observed a positive linear relationship with adult weight gain with an RR of 1.12 (95% CI: 1.05–1.19) for every 5‐kg increase. There is evidence that adult weight gain is associated with an increased risk of high‐risk and fatal prostate cancer, but only low weight gain is positively associated with low‐intermediate‐risk prostate cancer. Abstract : What's new? Evidence suggests that lifestyle and dietary factors play an important role in the etiology of prostate cancer. However, the association between adult weight gain and risk of prostate cancer has not been widely studied and remains unclear. The meta‐analysis presented here quantitatively assesses the dose‐response relationship between adult weight gain and risk of prostate cancer. The results suggest that adult weight gain is associated with an increased risk of high‐risk and fatal prostate cancer, but only low weight gain is positively associated with low‐intermediate‐risk prostate cancer. Recognition of this risk is of great importance for clinical and public health practices.